PENGARUH METODE COOPERATIVE INTEGRATED READINGAND COMPOSITION (CIRC) TERHADAP KEMAMPUAN BERFIKIRKRITIS SISWA PADA PELAJARAN BIOLOGI KELAS VIII MTS. MU’ALLIMIN NW PANCOR - Nuraini Nuraini (UNIVERSITAS HAMZANWADI, 2016)
The purpose of this study was to determine the effect of cooperative integrated reading and composition (CIRC) methods on students' critical thinking skills in the biology class of viii mts. mu'allimin Nw pancor 2013/2014 learning year. This type of research is experimental research with experimental design design (pretest-posttest control group) population of this study were all students of class VIII MTs. Mualimin NW Pancor. The sample in this study was simple random sampling. Data collection techniques use tests, in the form of 5 questions. Data analysis techniques look at critical thinking skills using prerequisite tests (normality, homogeneity test) and hypothesis testing that is by t-test (t-test) The results of the research obtained are the posttest average values in the 77.53 experimental class and the 70.92 control class and the results of the normality test are the experimental class and the normally distributed controls. For the experimental class the value of X2 count (-27.93) X2 Table (11,070) and control class X2 count (-56,23) X2 Table (11,070). While the homogeneity shows that the two groups are homogeneous which is seen from the value of Fcount (1.5) F table (1.93). To test the hypothesis used the t-test formula. obtained by tcount t table (4,166 1,874). So it can be concluded that the use of cooperative learning methods of reading and composition (CIRC) influences towards students' critical thinking skills in the biii class biology class. mu'allimin Nw pancor 2013/2014 learning year.